Mental Health Literacy or Medicalization? The Impact of Psychology Content on TikTok on Generation Z Self-Diagnosis - Ahmad Syamsul Muarif (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
This integrative literature review examines whether psychology content on TikTok strengthens mental health literacy or promotes the medicalization of ordinary distress and self-diagnosis among Generation Z. Peer-reviewed publications from 2019 to July 2026 were traced through PubMed, Google Scholar, and publisher databases, supplemented by foundational literature on mental health literacy, medicalization, and media effects. Twenty-eight publications were analyzed thematically. The synthesis identifies a dual pathway. TikTok may increase access to psychological language, normalize help-seeking, reduce isolation, and connect young people with professional resources. Conversely, symptom checklists, decontextualized personal narratives, inaccurate information, and algorithmic repetition may encourage overidentification, self-labeling, health anxiety, and the interpretation of common emotional experiences as psychiatric disorders. Evidence does not support a simple deterministic conclusion: effects vary according to content quality, prior distress, digital health literacy, source credibility, and access to professional assessment. The article proposes an exposure–identification–algorithmic reinforcement–self-labeling–action model and recommends TikTok-informed assessment, nonjudgmental diagnostic clarification, and algorithmically informed mental health literacy in counseling and psychotherapy.